Does method of birth make a difference to when women resume sex after childbirth?. Issue 7 (27th February 2013) - McDonald, EA; Brown, SJ
<x xml:space="preserve">Abstract</x> Objective To investigate the timing of resumption of vaginal sex and assess associations with method of birth, perineal trauma and other obstetric and social factors. Design Prospective pregnancy cohort study of nulliparous women. Setting Melbourne, Australia. Sample A total of 1507 nulliparous women recruited in early pregnancy (≤24 weeks). Method Women were recruited from six public hospitals. Data from hospital records and self‐administered questionnaires at recruitment and 3, 6 and 12 months postpartum were analysed using univariable and multivariable logistic regression. Main outcome measure Resumption of vaginal sex. Results Sexual activity was resumed earlier than vaginal sex, with 53% resuming sexual activity by 6 weeks postpartum, and 41% attempting vaginal sex. By 8 weeks a majority of women had attempted vaginal sex (65%), increasing to 78% by 12 weeks, and 94% by 6 months. Compared with women who had a spontaneous vaginal birth with an intact perineum, women who had a spontaneous vaginal birth with an episiotomy (adjusted odds ratio 3.43, 95% confidence interval 1.9–6.2) or sutured perineal tear (adjusted odds ratio 3.18, 95% confidence interval 2.1–4.9) were more likely not to have resumed vaginal sex by 6 weeks postpartum. Similarly, women who had an assisted vaginal birth or caesarean section had raised odds of delaying resumption of sex. Conclusions Most women having a first birth do not resume vaginal sex until later than 6 weeks postpartum. Women who have an operative vaginal birth, caesarean section or perineal tear or episiotomy appear to delay longer.